2023
DOI: 10.1177/87564793231156384
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hypertension and Diabetes on Ophthalmic Artery Hemodynamics

Abstract: Objective: Hypertensive and diabetic patients are at higher risk of developing ocular complications. Color and spectral Doppler, as a noninvasive technique, can be used to monitor and access the ophthalmic artery (OA) and its hemodynamic characteristics. The aim of this study was to investigate the hemodynamics of OA in diabetes and hypertension. Materials and Methods: This cross-sectional study was conducted at the University of Lahore sonography clinic. The patients were investigated using Toshiba Xario with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…This is emphasized by reviewing the reported pathological variations, in the hemodynamics of the ophthalmic artery, that were recorded in a larger cohort (N = 41) of patients with diabetes and hypertension. 23 In this study, Table 4 showed a moderately positive correlation between the PSV (r = 0.592) and RI (r = 0.475) of the right and the left CRA, while a weak posi tive correlation was noted in EDV (r = 0.258) and PI (r = 0.269) of the right and the left CRA. This is a comparable study result that also showed a positive correlation of Doppler indices within the right and left CRA, among a cohort of women with preeclampsia.…”
Section: Discussionsupporting
confidence: 47%
“…This is emphasized by reviewing the reported pathological variations, in the hemodynamics of the ophthalmic artery, that were recorded in a larger cohort (N = 41) of patients with diabetes and hypertension. 23 In this study, Table 4 showed a moderately positive correlation between the PSV (r = 0.592) and RI (r = 0.475) of the right and the left CRA, while a weak posi tive correlation was noted in EDV (r = 0.258) and PI (r = 0.269) of the right and the left CRA. This is a comparable study result that also showed a positive correlation of Doppler indices within the right and left CRA, among a cohort of women with preeclampsia.…”
Section: Discussionsupporting
confidence: 47%